Titanium Dioxide Nanoparticles Induce Inhibitory Effects against Planktonic Cells and Biofilms of Human Oral Cavity Isolates of Rothia mucilaginosa, Georgenia sp. and Staphylococcus saprophyticus - Saher Fatima; Khursheed Ali; Bilal Ahmed; Abdulaziz A. Al Kheraif; Asad Syed; Abdallah M. Elgorban; Javed Musarrat; Jintae Lee (MDPI AG, 2021)
Multi-drug resistant (MDR) bacterial cells embedded in biofilm matrices can lead to the development of chronic cariogenesis. Here, we isolated and identified three Gram-positive MDR oral cocci, (1) SJM-04, (2) SJM-38, and (3) SJM-65, and characterized them morphologically, biochemically, and by 16S rRNA gene-based phylogenetic analysis as Georgenia sp., Staphylococcus saprophyticus, and Rothia mucilaginosa, respectively. These three oral isolates exhibited antibiotic-resistance against nalidixic acid, tetracycline, cefuroxime, methicillin, and ceftazidime. Furthermore, these Gram positive MDR oral cocci showed significant (p < 0.05) variations in their biofilm forming ability under different physicochemical conditions, that is, at temperatures of 28, 30, and 42 °C, pH of 6.4, 7.4, and 8.4, and NaCl concentrations from 200 to 1000 µg/mL. Exposure of oral isolates to TiO2NPs (14.7 nm) significantly (p < 0.05) reduced planktonic cell viability and biofilm formation in a concentration-dependent manner, which was confirmed by observing biofilm architecture by scanning electron microscopy (SEM) and optical microscopy. Overall, these results have important implications for the use of tetragonal anatase phase TiO2NPs (size range 5-25 nm, crystalline size 13.7 nm, and spherical shape) as an oral antibiofilm agent against Gram positive cocci infections. We suggest that TiO2NPs pave the way for further applications in oral mouthwash formulations and antibiofilm dental coatings.